Complete ophthalmoplegia in Ipilmumab and Nivolumab combination treatment for metastatic melanoma. (3rd September 2018) - Alnabulsi, Reem; Hussain, Ahsen; DeAngelis, Dan
ABSTRACT: Ipilimumab and Nivolumab are novel monoclonal antibodies that have recently been used successfully for treatment of metastatic melanoma. Ipilimumab is a human monoclonal antibody against Cytotoxic T Lymphocyte Antigen 4 (CTLA4) receptor, which suppresses T-cell proliferation and stimulates an inflammatory response against cancer cells. Nivolumab is an IgG4 monoclonal antibody against the cytotoxic T lymphocyte associated programmed death 1 receptor (PD-1). Ipilimumab and Nivolumab combination treatment has been shown to induce remission and prolong survival in patients with metastatic melanoma. The side effect profile of these medications has not been well studied. One entity of the side effects reported in the literature is immune-related adverse events (irAEs). There have been few case reports where these events were serious and irreversible. In this case report, we describe a fatal and severe diffuse panmyositis that involved the cardiac, respiratory, and extraocular muscles in a patient with metastatic melanoma secondary to combination treatment with Ipilimumab/Nivolumab.